2022
DOI: 10.3390/su142215415
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Coastal Changes and Assessing Protection Structures at the Damietta Promontory, Nile Delta, Egypt, to Secure Sustainability in the Context of Climate Changes

Abstract: The Damietta Promontory is a distinct coastal region in the Nile Delta Egypt, which comprises several communities with strategic economic projects. The promontory has experienced numerous inundation crises due to anthropogenic intervention and/or sea level rise (SLR). The recorded rate of erosion detected is from −18 to −53 m/yr., and −28 to −210 m/yr. along the promontory’s western and eastern coasts, respectively, with a total loss of about 3 km during the past century. It is critical to ensure sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Human activities have contributed to physical shoreline changes and their susceptibility to SLR [45,46], in which including building dams and extracting water for agricultural purposes also play a role in changes in SLR [14]. In Thailand, groundwater pumping increased SLR [17].…”
Section: Non-climatic Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Human activities have contributed to physical shoreline changes and their susceptibility to SLR [45,46], in which including building dams and extracting water for agricultural purposes also play a role in changes in SLR [14]. In Thailand, groundwater pumping increased SLR [17].…”
Section: Non-climatic Driversmentioning
confidence: 99%
“…The impact of structural infrastructure at Damietta Promontory, Egypt, in protecting coastal areas against SLR was studied in [45], using satellite images and historical data on changes in the shoreline. It was found that seawalls and detached breakwater bodies have effectively protected the coastline against SLR.…”
mentioning
confidence: 99%